Long-term outcome of deep brain stimulation in generalised dystonia: a series of 60 cases. Issue 12 (1st April 2014) - FitzGerald, J J; Rosendal, F; de Pennington, N; Joint, C; Forrow, B; Fletcher, C; Green, A L; Aziz, T Z
Abstract : Background: There is solid evidence of the long term efficacy of deep brain stimulation of the globus pallidus pars interna in the treatment of generalised dystonia. However there are conflicting reports concerning whether certain subgroups gain more benefit from treatment than others. We analysed the results of a series of 60 cases to evaluate the effects of previously proposed prognostic factors including dystonia aetiology, dystonia phenotype, age at onset of dystonia, and duration of dystonia prior to treatment. Methods: 60 patients with medically intractable primary or secondary generalised dystonia were treated with deep brain stimulation of the globus pallidus pars interna during the period 1999–2010 at the Department of Neurosurgery in Oxford, UK. Patients were assessed using the Burke-Fahn-Marsden (BFM) Dystonia Rating Scale prior to surgery, 6 months after implantation and thereafter at 1 year, 2 years and 5 years follow-up. Results: The group showed mean improvements in the BFM severity and disability scores of 43% and 27%, respectively, by 6 months, and this was sustained. The results in 11 patients with DYT gene mutations were significantly better than in non-genetic primary cases. The results in 12 patients with secondary dystonia were not as good as those seen in non-genetic primary cases but there remained a significant beneficial effect. Age of onset of dystonia, duration of disease prior to surgery, and myoclonic versus torsional disease phenotype had no significant effect on outcome. Conclusions: The aetiology of dystonia was the sole factor predicting a better or poorer outcome from globus pallidus pars interna stimulation in this series of patients with generalised dystonia. However even the secondary cases that responded the least well had a substantial reduction in BFM scores compared with preoperative clinical assessments, and these patients should still be considered for deep brain stimulation.